Development of 3D CAD/FEM Analysis System for Natural Teeth and Jaw Bone Constructed from X-Ray CT Images - Aki Hasegawa; Akikazu Shinya; Yuji Nakasone; Lippo V. J. Lassila; Pekka K. Vallittu; Akiyoshi Shinya (International Journal of Biomaterials)
A three-dimensional finite element model of the lower first premolar, with the three layers of enamel, dentin, and pulp, and the mandible, with the two layers of cortical and cancellous bones, was directly constructed from noninvasively acquired CT images. This model was used to develop a system to analyze the stresses on the teeth and supporting bone structure during occlusion based on the finite element method and to examine the possibility of mechanical simulation.